2020
DOI: 10.1136/bjsports-2019-100912
|View full text |Cite
|
Sign up to set email alerts
|

One small step for man, one giant leap for men’s health: a meta-analysis of behaviour change interventions to increase men’s physical activity

Abstract: ObjectiveTo determine the effects of behaviour change interventions on men’s physical activity (postintervention), sustained change in physical activity behaviour (≥12 months postintervention) and to identify variations in effects due to potential moderating variables (eg, theoretical underpinning, gender-tailored, contact frequency).DesignSystematic review with meta-analysis. Pooled effect size (Cohen’s d) was calculated assuming a random-effects model. Homogeneity and subsequent exploratory moderator analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 88 publications
4
23
0
1
Order By: Relevance
“…The results also con rm previous qualitative work describing how men with prostate cancer who take part in a football intervention appreciate being able to share new stories from training and the value adding aspects for their husband and father operating predominately in the domestic sphere [22,25]. Moreover, the results con rm the ndings of a recent meta-synthesis of various exercise interventions and their effect on male perception of masculinity, body image, and personal identity, which concluded that exercise can facilitate a process of self-re ection secondary to changes in physique and help to re-establish male self-e cacy [26,27] .…”
Section: Discussionsupporting
confidence: 75%
“…The results also con rm previous qualitative work describing how men with prostate cancer who take part in a football intervention appreciate being able to share new stories from training and the value adding aspects for their husband and father operating predominately in the domestic sphere [22,25]. Moreover, the results con rm the ndings of a recent meta-synthesis of various exercise interventions and their effect on male perception of masculinity, body image, and personal identity, which concluded that exercise can facilitate a process of self-re ection secondary to changes in physique and help to re-establish male self-e cacy [26,27] .…”
Section: Discussionsupporting
confidence: 75%
“…For example, increases in physical activity we observed may be linked to use of the Garmin device (i.e., self-monitoring), or the motivational messages, and the support and encouragement within and between participating workplace groups should not be ignored. A recent meta-analysis indicated that interventions with more behavior change techniques and gender-sensitive designs were associated with greater increases in physical activity among men, and among 12 studies that included follow-up assessments 12 or more months post-intervention, there was evidence that physical activity increases were sustained (Sharp et al, 2020). The baseline level of MVPA was also relatively high, which may have limited the ability of participants to further increase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Within male-dominated workplaces there are often normative frames related to physical work (e.g., heavy lifting and working with hand-held tools) (Lewis, 2013) and doing overtime (i.e., feelings of pressure or obligation to work long hours) (Bunjo et al, 2020); the net effect of such cultures is that other forms of physical activity and sleep are compromised (Seaton et al, 2018; Soprovich et al, In review). Few workplace programs take into consideration masculine norms or incorporate men’s preferences or interests; yet, growing evidence suggests that programs designed using a gender-tailored approach are effective for reaching men (Bottorff et al, 2015; Sayers et al, 2019; Sharp et al, 2020). In particular, it has been argued that leveraging positive and strength-based aspects of masculinity (e.g., male relational styles, use of humor, group orientation of men) may increase men’s specific engagement with health promotion (Kiselica & Englar-Carlson, 2010; Seidler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the success of lifestyle interventions offered in collaboration with professional sports clubs/teams to engage men in lifestyle changes have been linked to the masculine values and virtues entrenched in the physical and sociocultural environments that surround popular male sports [6][7][8]. There is also a growing body of evidence that tailoring of the content and delivery of lifestyle interventions to reflect men's preferences and needs also increases the engagement with and effectiveness of programs offered to men [9]. Although these are promising developments in this nascent field, further development and evaluation of these approaches to men's lifestyle interventions are needed to ensure their fit for implementation in new contexts and with diverse groups of men.…”
Section: Introductionmentioning
confidence: 99%